KONSUMSI MAKANAN PENDUDUK INDONESIA DITINJAU DARI NORMA GIZI SEIMBANG (FOOD CONSUMPTION IN TERM OF THE NORM OF BALANCED NUTRITION) - Amalia Safitri; Abas Basuni Jahari; Fitrah Ernawati (Persagi, 2016)
Currently Indonesia is facing double burden nutrition problems, undernutrition and overnutrition.The Riskesdas, national basic health survey in 2013 the prevalence of underweight is 19.6 percent and 11.9 percent overweight. One of the causes of malnutrition is a problem in selecting healthy food that can lead to problems in food variety, proportion and adequacy required by the body. The purpose of this analysis is to assess food consumption pattern of the population in both quality and quantity which is a representation of the first pillar of balanced nutrition guide (Pedoman Gizi Seimbang). Data from the Individual Food Consumption Survey (SKMI) in 2014 was used for this analysis. The diversity of food is analyzed based on the types of food consumed, the proportion of consumption data obtained from the consumption of carbohydrate, protein and fat, and the adequacy energy consumption as evaluated based on total energy consumption of the sample compared to Dietary Allowances (RDA). The results showed that only food variety is in better situation than the proportion and energy adequacy Recommendation,nutrition education should be intensified either through formal channel (via schools or other institution) or informal channel (pengajian, arisan, karang taruna, majlis taklim, sekolah minggu di gereja) conveying the messages of balanced nutrition. Saat ini Indonesia disebut menghadapi permasalahan gizi ganda, yaitu adanya masyarakat yang kekurangan gizi, namun sebaliknya ada juga yang kelebihan. Berdasarkan data Riskesdas tahun 2013 prevalensi underweight sebesar 19,6 persen dan kegemukan sebesar 11,9 persen. Salah satu penyebab dari kejadian ini adalah adanya kesalahan dalam pola makan yang tidak memperhatikan keragaman, proporsi dan kecukupan energi yang dibutuhkan oleh tubuh.Tujuan dari analisis ini adalah untuk melihat bagaimana pola konsumsi penduduk baik kualitas maupun kuantitasnya yang merupakan cerminan dari pilar pertama gizi seimbang. Analisis ini menggunakan data dari Survei Konsumsi Makanan Individu (SKMI) tahun 2014. Keragaman makanan didapatkan dari data hidangan dan jenis bahan makanan, proporsi konsumsi didapatkan dari data konsumsi bahan makanan sumber karbohidrat (KH), protein dan lemak dan data kecukupan didapatkan dari total energi yang dikonsumsi dibandingkan dengan angka kecukupan gizi (AKG). Hasil yang didapat dari analisis ini secara umum keragaman konsumsi makanan penduduk di Indonesia sudah baik, namun pada proporsi dan kecukupan konsumsi masih kurang. Saran dari hasil analisis ini adalah perlu digalakkannya pedoman gizi seimbang dan lebih memahami pentingnya menjaga kualitas dan kuantitas konsumsi makanan agar sehat dan terhindar dari penyakit.